Impact of Predator Switching in the Disease Outbreak of an Eco-Epidemiological System - Saikh, Aktar; Gazi, Nurul Huda (Journal of Applied Nonlinear Dynamics, 2026)
We introduce an ecological improvement of an eco-epidemiological model by improving the predation principles through predator switching between susceptible and infected prey. The model is analyzed for stability around the uninfected and coexisting equilibria to evaluate the thresholds that control the extinction and coexistence of the species. Next, we investigate the improved model to interpret the effect of changing the functional responses through predator switching. Applying the Arzelà-Ascoli theorem, we analyze the dynamics of the system around the origin. Numerical simulations are performed to validate the analytical findings. Finally, we conclude some eco-epidemiological comments made through mathematical and numerical observations.